Professores formadores de pedagogos para o ensino de Geografia nos anos iniciais do ensino fundamental: o que eles ensinam? - Helania Martins de Souza (2024)
Training in Pedagogy qualifies you for teaching in the early years of elementary school. At this school stage, the National Common Curricular Base (BNCC) reaffirms Geography as a specific subject and lists knowledge to be worked on during classes. In this research, it was found that in Pedagogy courses, teachers responsible for teaching geographic knowledge may have different backgrounds. In the Pedagogy courses at the State University of Minas Gerais (UEMG), the universe of this investigation, we found that the aforementioned teachers have training in Geography, Pedagogy or History. This reality made us question the relationship between the training of the trainer and the teaching of Geography for Pedagogues, future teachers in the early years of elementary school. The research that constitutes this work was developed based on the following question: What can training paths reveal about the PCK of teachers who teach Geography subjects in Pedagogy courses? To this end, we defined as a general objective the identification of possible relationships between the PCK of the teacher who teaches geography in Pedagogy and the contents he teaches in Pedagogy courses. As specific objectives, we consider: i- analysis of theoretical bases and curricular references, in order to identify what such sources consider relevant for the teaching of Geography in the Early Years; ii- identification of content, geographic concepts, pedagogical methodologies that guide the teaching of geographic knowledge in Pedagogy courses; iii- understanding and analysis of the relationships between the PCK of pedagogue trainers, what they teach to pedagogues in training and the knowledge required to teach Geography in the initial years of primary education. We used Pedagogical Content Knowledge – PCK (SHULMAN, 1986; 1987) as a theoretical framework. We chose as research subjects teachers of the Fundamentals and Methodologies of Teaching Geography subjects from different units at UEMG. For methodological purposes, we articulate the theoretical bases and curricular documents referring to the teaching of Geography in the early years of elementary school; to teachers' teaching plans and Pedagogical Projects of Pedagogy Courses. The training paths of the research subjects were obtained from the Lattes Curriculum and interviews with teachers. The data collected via semi-structured interviews went through the Discourse Analysis methodology based on Bakhtin and his Circle. The interviews were carried out in person, using an adaptation of the Repertory Grid technique to identify the pedagogical knowledge of the research subjects' content. As results, we anticipate that teacher training in the specific teaching area of Geography and their training path in Education implies a better adaptation to what we believe is aligned with the geographic knowledge necessary for the training of pedagogues.